2007
DOI: 10.1007/s11055-007-0152-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionotropic glutamate receptor channel blockers on the development of pentylenetetrazol kindling in mice

Abstract: Experiments on mice were performed to study the ability of monocationic and dicationic adamantane and phenylcyclohexyl derivatives to prevent the development of kindling induced by i.p. administration of pentylenetetrazol (Corasol, 35 mg/kg). The monocationic phenylcyclohexyl derivative IEM-1921 effectively slowed the development of kindling, this being seen over a wide range of doses (0.0001-0.1 micromol/kg). A monocationic adamantane derivative (memantine), also a selective non-competitive blocker of NMDA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Previously reported data on the protective efficacy of IEM‐1921 in PTZ tests are scarce. One group reported that IEM‐1921 protected only four of 10 mice at a dose of 30 mg/kg in a PTZ seizure test (s.c. injection at the CD97 convulsant dose [85 mg/kg] of PTZ; Rogawski et al, ) and that it was highly effective at low concentrations against the development of PTZ kindling (Lukomskaya et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported data on the protective efficacy of IEM‐1921 in PTZ tests are scarce. One group reported that IEM‐1921 protected only four of 10 mice at a dose of 30 mg/kg in a PTZ seizure test (s.c. injection at the CD97 convulsant dose [85 mg/kg] of PTZ; Rogawski et al, ) and that it was highly effective at low concentrations against the development of PTZ kindling (Lukomskaya et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that ketamine, another NMDA receptor channel blocker, is useful in the treatment of refractory status epilepticus (Dorandeu et al, ). A structurally similar compound, 1‐phenylcyclohexylamine (IEM‐1921), is a more potent anticonvulsant and causes less motor impairment than ketamine at anticonvulsant doses (Rogawski et al, ; Blake et al, ; Parsons et al, ; Lukomskaya et al, ; Kim et al, ). However, its anticonvulsant and neuroprotective properties have not been fully elucidated.…”
mentioning
confidence: 99%
“…kindling starting at a dose of 3 mg/kg i.p. [ 156 ]. Similar effects were seen against NMDA convulsions whereas ataxic side effects were first seen at doses some 6-fold higher [ 157 , 235 ].…”
Section: Secondary Pharmacodynamicsmentioning
confidence: 99%
“…In particular, it has been revealed that dicationic compounds possess a selective blocking capability against CP AMPARs [21]; the maximum activity was demonstrated by com pounds with the distance between nitrogen atoms equal to five methylene groups [22]. The capability of quite a number of newly developed channel blockers of CP AMPA and/or NMDA receptors to prevent experimentally induced convulsive and cataleptic states in rats and mice has been studied as well [23][24][25][26][27]. At the same time, it was found that the efficiency of therapy for such states with selective CP AMPAR blockers was altogether less than with NMDAR blockers.…”
mentioning
confidence: 99%
“…At the same time, it was found that the efficiency of therapy for such states with selective CP AMPAR blockers was altogether less than with NMDAR blockers. More over, under certain conditions CP AMPAR blockers even contributed to the expression of pathological symptoms [23].…”
mentioning
confidence: 99%